Presence-absence sampling decision rules for the damage caused by the coffee leaf miner (Leucoptera coffeella (Guérin-Menéville, 1842) - Villacorta, Amador; Gutierrez, Andrew Paul (Pesquisa Agropecuaria Brasileira, 2014)
An accurate but simple presence-absence sampling method is proposed for estimating densities of lesions on leaves, caused by the coffee leaf miner (Leucoptera coffeella (Guérin - Menéville, 1842). This sampling method enables IPM Scouts to quickly determine whether the infestation has reached the action threshold of one leaf miner lesion per leaf. The accuracy of the sample size can also be determined.
Keywords: binomial sampling; Poisson distribution